2002
DOI: 10.1302/0301-620x.84b1.0840093
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for survival and local control in chondrosarcoma of bone

Abstract: We studied 153 patients with non-metastatic chondrosarcoma of bone to determine the risk factors for survival and local tumour control. The minimum follow-up was for five years; 52 patients had axial and 101 appendicular tumours. Surgical treatment was by amputation in 27 and limb-preserving surgery in 126. The cumulative rate of survival of all patients, at 10 and 15 years, was 70% and 63%, respectively; 40 patients developed a local recurrence between 3 and 87 months after surgery and 49 developed metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 0 publications
8
60
3
1
Order By: Relevance
“…In summary, patients with a local recurrence have a worse survival rate, accompanied by a higher rate of distant metastases. This phenomenon is well known in the literature too [19, 25]. …”
Section: Discussionmentioning
confidence: 74%
“…In summary, patients with a local recurrence have a worse survival rate, accompanied by a higher rate of distant metastases. This phenomenon is well known in the literature too [19, 25]. …”
Section: Discussionmentioning
confidence: 74%
“…These data strongly suggest the existence of cancer stem cells possibly with mesenchymal stem cells or fibroblast markers. Although most of the literature on chondrosarcoma has confirmed that adequate surgery is the mainstay of treatment for local tumour control, which itself constitutes a risk factor for survival, an additional feature of chondrosarcoma is also the high level of local recidive even in case of adequate surgery [3840]. This feature is also in favour of the existence of cancer stem cells in the bone marrow which may remain dormant until some yet unknown signals promote their growth or/and metastasis formation in bone tissue.…”
Section: The Bone Niche Of Chondrosarcomamentioning
confidence: 99%
“…Chondrosarcomas can progress from low grade to high grade, which is reflected by increased cellularity, nuclear atypia, mucomyxoid matrix changes, and increased vascularization [3, 4]. Low-grade chondrosarcomas are locally aggressive but rarely metastasize [5].…”
Section: Introductionmentioning
confidence: 99%
“…Low-grade chondrosarcomas are locally aggressive but rarely metastasize [5]. By contrast, high-grade chondrosarcomas often metastasize and are lethal in most patients [3]. The molecular mechanisms involved in the progression to high-grade chondrosarcoma are beginning to be unravelled [1].…”
Section: Introductionmentioning
confidence: 99%